2019
DOI: 10.1038/s41593-019-0374-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cortical–amygdala projections drive reward value encoding and retrieval

Abstract: The value of an anticipated rewarding event is a crucial component of the decision to engage in its pursuit. But little is known of the networks responsible for encoding and retrieving this value. Using biosensors and pharmacological manipulations, we found that basolateral amygdala (BLA) glutamatergic activity tracks and mediates the encoding and retrieval of the state-dependent incentive value of a palatable food reward. Projection-specific, bidirectional chemogenetic and optogenetic manipulations revealed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(148 citation statements)
references
References 67 publications
8
140
0
Order By: Relevance
“…A hallmark of OFC function is its contribution to outcome evaluation and updating, with increases in OFC activity observed during outcome presentation (Jones et al, 2012;Stalnaker et al, 2014Stalnaker et al, , 2015Stalnaker et al, , 2018. Recent works have shown that inhibition of OFC activity during periods of reward presentation prevent outcome evaluation and updating (Baltz et al, 2018;Malvaez et al, 2019). Here, we observed large increases in OFC activity during outcome evaluation periods and this increase was reduced following alcohol dependence (Figure 3).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A hallmark of OFC function is its contribution to outcome evaluation and updating, with increases in OFC activity observed during outcome presentation (Jones et al, 2012;Stalnaker et al, 2014Stalnaker et al, , 2015Stalnaker et al, , 2018. Recent works have shown that inhibition of OFC activity during periods of reward presentation prevent outcome evaluation and updating (Baltz et al, 2018;Malvaez et al, 2019). Here, we observed large increases in OFC activity during outcome evaluation periods and this increase was reduced following alcohol dependence (Figure 3).…”
Section: Discussionsupporting
confidence: 60%
“…Several lines of evidence implicate the OFC as a key regulator of the neurobiological circuitry supporting decision-making processes (Fellows, 2007;Wallis, 2007;Gremel & Costa, 2013;Stalnaker et al, 2015;Padoa-Schioppa & Conen, 2017). In particular, recent works have supported the hypothesis that the OFC may serve as a cognitive map, supporting inference of unobservable learned information necessary to guide flexible behavior (Wilson et al, 2014;Baltz et al, 2018;Schuck et al, 2016;Niv, 2019;Malvaez et al, 2019;Zhou et al, 2019). Indeed, OFC has long been known to convey unobservable information about changes in outcome values and their contingent choices or actions to guide decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have begun to identify the putative neural structures and circuits supporting this function, with several lines of evidence suggesting the orbitofrontal cortex (OFC) plays a key role [1][2][3][4] . Recent studies have also demonstrated a high degree of functional heterogeneity within the OFC [5][6][7][8][9][10] , yet how these functionally distinct OFC subregions might differentially contribute to its function as a cognitive map of task space has never been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, BN showed reduced connectivity in the right hemisphere between the basolateral amygdala and the dorsal anterior insula, and ventral striatum (Frank et al, 2016). A recent study shows that basolateral amygdala connections with the lateral and medial OFC are necessary for the encoding and retrieving of positive values of rewards respectively (Malvaez et al, 2019). It could be that the reduced connectivity of the amygdala shows that BN, when exposed to acute stress, have more difficulty with retrieving the positive reward value.…”
Section: Negative Affectmentioning
confidence: 99%